PEMBERDAYAAN MASYARAKAT MELALUI PEMBANGUNAN BERBASIS “SKP2” TERPADU DALAM MEWUJUDKAN “BLUE ECONOMY” MASYARAKAT PESISIR PANTAI DAN KEPULAUAN YANG TANGGUH DAN SEJAHTERA (TARA) - Linda Suwarni; Helman Fachri; Iskandar Arfan (Universitas Muhammadiyah Pontianak, 2017)
Sungai Raya Kepulauan District is located on the coast separately and away from the Bengkayang Capital. The majority of the population including the coastal communities who work as fishermen. The coastal area has great potential but has not been used optimally. As a result, various problems arose, for example, the low level of health in the village, lack of public education because of limited school and lack of community economy further aggravate the situation. Therefore, we need a new concept for the development of coastal areas, namely the